Effects of a 6-week neuromuscular ankle training program on the Star Excursion Balance Test for basketball players - Borao, O.; Planas, A.; Beltran, V.; Corbi, F. (Apunts Medicina de l'Esport, 2015)
Background: The largest percentage of injuries in basketball affect the lower limbs, specially the ankle joint, and this is the major cause of missed days of training during a season. Moreover, ankle injuries can increase the risk factor of recurrent injuries.